Transcriptomic and metabolomic studies on the protective effect of molecular hydrogen against nuclear electromagnetic pulse-induced brain damage - Ma, Long; Tian, Shuo; Zhang, Hai-Ling; Wang, Jing-Yi; Wang, Jia-Wen; Yan, Hong-Li; Hu, Xu-Guang; Shao, Qi; Guo, Jia-Ming (Frontiers in Public Health, 2023)
Background: Excessive doses of electromagnetic radiation pose a negative impact on the central nervous system and lead to mental disorders. Molecular hydrogen can scavenge intracellular hydroxyl radicals, acting as an antioxidant, anti-apoptotic and anti-inflammatory agent. We seek to assess the capability of molecular hydrogen to ameliorate brain damage induced by electromagnetic radiation. Methods: Male wild-type rats were divided into four groups: the control group, the H2 (Molecular hydrogen) group, the NEMP (nuclear electromagnetic pulse) group and the NEMP+H2 group. Rats in the H2 group and the NEMP+H2 group were fed with saturated hydrogen-rich water from three days before NEMP exposure (electromagnetic field intensity 1000 kV/m, rising edge 20 ns and pulse width 200 ns) to the day of sacrifice. One day after exposure, animal behavior experiments were performed, and samples for transcriptomics and metabolomics analysis were collected. Seven days after exposure, histopathological experiments were conducted. Results: The data from the elevated plus maze and the open field test showed that NEMP exposure elicited anxiety-like behavior in rats, which could be alleviated by H2 treatment. Histopathological results manifested that NEMP exposure-induced injuries of the neurons in the hippocampus and amygdala could be attenuated by H2 treatment. Transcriptomic results revealed that NEMP exposure had a profound effect on microtubule structure in the brain. And the combined analysis of transcriptomics and metabolomics showed that H2 has a significant impact on the neuroactive ligand-receptor interaction, synaptic vesicle cycle and synapse etc. Moreover, it was indicated that the glutathione metabolic pathway played a vital role in the NEMP exposure-induced damage and the protective activity of H2. Conclusions: H2 is identified as a potent agent against NEMP exposure-induced brain damage and has the potential to be a promising electromagnetic radiation protectant.